What’s Up, Tiger Lily? On Woody Allen and the Screen Translator’s Trojan Horse - Fraser, Ryan (TTR, 2010)
Woody Allen made his transition from stand-up comedy to cinema not as an author, but as a dialogue adaptor and film dubber. In 1966, he transformed a Japanese spy thriller into an American comedy by removing the film’s original dialogue and soundtracks, and then synchronizing a new dialogue of his own penning with the original film’s images. The result was What’s Up, Tiger Lily? (1966), a film where Allen forces a cast of unwitting Japanese characters to act out one narrative visibly as they speak out another audibly. The film suggests a number of intriguing theoretical vectors for those interested in the subject of screen translation as a mode of intercultural appropriation (or misappropriation). What’s Up, Tiger Lily?, first of all, is a comedic exploration of authorial status in cinema. Indeed, the lesser status of “re-writer” becomes Allen’s cover, a way to avoid taking responsibility for a film that not only indulges in the most counterintuitive of experiments in the sound-image relationship, but also creates a particularly condescending form of Asian exploitation. Perhaps most important, however, is the perspective that the film offers on the voice-image antagonism implicit in any foreign-language dubbed film. Allen’s film may well offer a way for theory to transcend the aura of negativity with which academic discourse tends to surround the practice of dubbing, specifically by putting the latter to use in the service of intercultural parody. Michael Cronin’s latest work on globalization and Hollywood (2009) offers some helpful concepts for examining Allen’s film.